Biphasic insulin aspart in type 2 diabetes mellitus: an evidence-based medicine review. - Gough, S; Tibaldi, J (2007)
The efficacy benefits of biphasic insulin aspart formulation (BIAsp 30) in patients with diabetes mellitus have been reported in several studies. BIAsp 30 has been shown to be more effective in terms of glycaemic control than standard biphasic human insulin 30 (BHI 30). In addition to gauging the treatment in terms of clinical evidence of benefits provided, it is also important to evaluate the strength of the evidence supporting the therapeutic improvements offered by BIAsp 30. In this paper, we evaluated the strength of the available data that relate to the use of BIAsp 30 in the treatment of patients with type 2 diabetes based on a comprehensive literature review. Selected publications that provided relevant data were obtained via a literature search and from the manufacturer, Novo Nordisk. These were graded in terms of the strength of the evidence they provided using the Oxford Centre for Evidence-Based Medicine (CEBM) system in the following categories: (i) twice-daily use versus basal insulin; (ii) twice-daily use versus other treatments; (iii) once-daily use; (iv) thrice-daily use; (v) use in combination with thiazolidinediones; and (vi) use in comparison with BHI 30. A total of 30 publications for BIAsp 30 were identified and graded. For the majority of categories (four out of six), the evidence supporting the use of BIAsp 30 was given an overall CEBM grade of A (highest quality); evidence supporting clinical efficacy in the other two categories (twice-daily use versus basal insulin and thrice-daily BIAsp 30 administration) was graded B. In most of the studies examined, the efficacy of BIAsp 30 was evaluated in terms of glycaemic control (glycosylated haemoglobin [HbA(1c)] reduction, proportion of patients achieving HbA(1c) target of <6.5% or <7%, fasting blood glucose, blood glucose profile and/or prandial and postprandial glucose increments). In some studies, efficacy was further evaluated using plasma insulin and glucose infusion rates, plasma C-peptide levels, mean serum fructosamine levels, postprandial hyperlipidaemia, overall well-being, treatment satisfaction and quality of life. Safety was evaluated using physical and laboratory investigations and assessment of incidence of adverse events, including, in many of the studies reviewed, specific evaluation of those events known to be associated with antidiabetic treatment, hypoglycaemia and weight gain. Strong evidence was provided for better glycaemic control with BIAsp 30 without increases in the incidence of major hypoglycaemia or nocturnal hypoglycaemic episodes. Overall, weight gain with BIAsp 30 was minimal and not significantly greater than with basal insulin or BHI 30. Thus, we can confirm that the reported efficacy and tolerability of BIAsp 30 in the treatment of diabetes based on a variety of clinical endpoints is supported by a good body of evidence relating to its use in different dosage regimens and in comparison with other insulin treatment regimens.